Time Budget Pressure, Audit Tenure, Ukuran Perusahaan, Spesialisasi Auditor, dan Kualitas Audit - Utami, I Gusti Ayu Agung Sintia; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi, 2023)
Audit quality is a measure of quality carried out by auditors who are in accordance with auditing standards and quality control systems. The auditor must have adequate audit quality so as to reduce the dissonance that occurs between management and shareholders. There are several factors that affect audit quality, namely time budget pressure, audit tenure, company size and auditor specialization. The purpose of this study was to empirically examine the effect of time budget pressure, audit tenure, company size and auditor specialization on audit quality in the property, real estate and building construction sectors listed on the Indonesia Stock Exchange in 2017-2019. The sample of this research is 49 companies using purposive sampling technique. The data analysis technique used in this study is logistic regression analysis. The results of the study show that time budget pressure and auditor specialization have no effect on audit quality. Meanwhile, audit tenure and firm size have a negative and significant effect on audit quality. Keywords: Time Budget Pressure; Audit Tenure; Company Size; Auditor Specialization; Audit Quality